Chitin isolated from yeast cell wall induces the resistance of tomato fruit to Botrytis cinerea. (1st November 2018) - Sun, Cui; Fu, Da; Jin, Lifei; Chen, Mengyi; Zheng, Xiaodong; Yu, Ting
Highlights: The chemical structure of chitin was characterized by 13 C CP/MAS NMR and FT-IR. Chitin efficiently inhibited gray mold rot in tomato fruit. Chitin treatment promoted the accumulation of ROS and callose deposition. Chitin activated defense-related enzymes and the corresponding genes. The SA signaling pathway might be involved in chitin-induced disease resistance. Abstract: The present study characterized a cell wall chitin from Saccharomyces cerevisiae and investigated the effect of a postharvest chitin treatment on disease resistance against Botrytis cinerea infection in tomato fruit and the possible mechanisms involved. The results indicated that treatment with chitin could effectively induce strong resistance against gray mold rot caused by B. cinerea in tomato fruit. Moreover, chitin treatment promoted the accumulation of ROS and callose deposition. The activities of six defense-related enzymes, including superoxide dismutase, catalase, peroxidase, phenylalanine ammonia-lyase, β-1, 3-glucanase and chitinase, along with the expression of these corresponding genes, were markedly enhanced in the chitin-treated fruit. Meanwhile, the key enzyme genes of SA biosynthesis and signal transduction pathway were found up-regulated in the chitin treatment. Therefore, these results suggest that the increased disease resistance of tomato fruit after chitin treatment during storage might be attributed to an elicitation of defense response as mentioned above in fruit.